Sex differences in the course of schizophrenia across diverse regions of the world - Novick D; Montgomery W; Treuer T; Moneta MV; Haro JM (Neuropsychiatric Disease and Treatment)
Diego Novick,1 William Montgomery,2 Tamas Treuer,3 Maria Victoria Moneta,4 Josep Maria Haro4 1Eli Lilly and Company, Windlesham, Surrey, UK; 2Eli Lilly Australia Pty Ltd, West Ryde, NSW, Australia; 3Eli Lilly and Company, Neuroscience Research, Budapest, Hungary; 4Parc Sanitari Sant Joan de Déu, CIBERSAM, Universitat de Barcelona, Barcelona, Spain Abstract: This study explores sex differences in the outcomes of patients with schizophrenia (clinical/functional remission and recovery) across diverse regions of the world (Northern Europe, Southern Europe, Central and Eastern Europe, Latin America, East Asia, and North Africa and the Middle East). Data (n=16,380 for this post hoc analysis) were taken from the World-Schizophrenia Health Outcomes Study. In most regions, females had a later age at first service contact for schizophrenia, a lower level of overall/negative symptom severity, lower rates of alcohol/substance abuse and paid employment, and higher percentages of having a spouse/partner and independent living. Overall, females had slightly higher rates of clinical remission (58.0% vs 51.8%), functional remission (22.8% vs 16.0%), and recovery (16.5% vs 16.0%) at 36 months (P<0.001 for all). This pattern was consistently observed in Southern Europe and Northern Europe even after controlling for baseline sex differences, but not in other regions. In Central and Eastern Europe, rates of clinical remission were higher in females at 36 months, but those of functional remission and recovery were similar between males and females. The opposite was observed for Latin America. In East Asia, sex differences were rarely observed for these outcomes. Finally, in North Africa and the Middle East, sex differences in these outcomes were pronounced only in regression analyses. These regional variations shed light on the importance of psychosocial and cultural factors and their effects on sex in the prognosis of schizophrenia. Keywords: sex, remission, recovery, region, schizophrenia, world